Organizing modernity : new Weberian perspectives on work, organization, and society - Ray, Larry J.; Reed, M. I. (Michael I.) (Routledge, 1994)
This book provides a re-evaluation of Weber's work on the current debates about the institutional and organizational dynamics of modernity, offering interpretations of his work which emphasize the reality of modernity as a dual process.